Management Strategies of MSME Actors In Human Resource Management And Intellectual Property Rights Protection: Case Study : In the Creative Sector of the Blitar City Government Area - Trioko, Sunan; Lailin, Ulva Roifatul; Amelia, Cindy Ayu (AKSIOMA : Jurnal Manajemen, 2025)
The purpose of this study is to evaluate the strategies of human resource management (HR) and intellectual property rights (IPR) protection implemented by micro, small, and medium enterprises (MSMEs) in the creative wood sector, especially Griya Kayu. Data was collected through observation, documentation, and in-depth interviews. Research shows that hands-on training and productivity-based incentive systems are still used informally to manage human resources. Although the practice is effective, this method does not guarantee progress in the long run. Since more than 97% of the workforce in Indonesia is employed by MSMEs, which account for more than 60% of the national GDP as well as high costs and information limitations, most MSME manufacturers have not registered their product brands and designs. They rely more on publications, which do not have sufficient legal force, as proof that they are genuine. Due to information and cost limitations, IPR protection has not been a priority. Recommendations include training in human resource management and the government should facilitate IPR registration. The research not only identifies strategies and challenges faced by MSMEs, but also makes practical suggestions for the sustainable development of key barriers such as capital limitations, lack of legal understanding, and access to information. However, with the support of the government and strategic partners such as NGOs and educational institutions, there are opportunities. Some of the micro, small, and medium enterprises (MSMEs) have succeeded in managing their businesses, including in the field of wooden handicraft accessories, drums, bags, and handicrafts sold around the Bungkarno Cemetery in Blitar City.
Keywords: MSME management; human resources; intellectual property rights; creative industry; Griya Kayu